2011
DOI: 10.1111/j.1528-1167.2011.03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomic correlates of psychogenic nonepileptic seizures: A cortical thickness and VBM study

Abstract: SUMMARYPurpose: Psychogenic nonepileptic seizures (PNES) are among the most common clinical manifestations of conversion disorder and consist of paroxysmal behavior that resembles epileptic seizures. Preliminary data from functional neuroimaging studies gave plausible evidence that limbic circuits and sensorimotor cortex might be engaged in conversion disorder. Nonetheless, no advanced magnetic resonance imaging (MRI) studies have focused on patients with PNES. Methods: We enrolled 20 consecutive patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 41 publications
(50 reference statements)
8
163
3
2
Order By: Relevance
“…Van der Kruijs and colleagues found stronger connectivity values between regions involved in emotion (insula), executive control (inferior-frontal and parietal cortices), and movement (precentral sulcus) [6]. Using voxel-based morphometry, Labate and colleagues [7] found abnormal cortical atrophy of the motor and premotor regions in the right hemisphere and the cerebellum bilaterally. Using EEG, Krishnan et al found "resetting" of brain dynamics in patients with ESs but not in patients with PSs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Van der Kruijs and colleagues found stronger connectivity values between regions involved in emotion (insula), executive control (inferior-frontal and parietal cortices), and movement (precentral sulcus) [6]. Using voxel-based morphometry, Labate and colleagues [7] found abnormal cortical atrophy of the motor and premotor regions in the right hemisphere and the cerebellum bilaterally. Using EEG, Krishnan et al found "resetting" of brain dynamics in patients with ESs but not in patients with PSs [8].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the right motor and premotor cortex as well as in the cerebellum thickness has been found in patients with pseudoepileptic seizures (Labate et al, 2012). Van der Kruijs described a greater connectivity between emotion-related areas (insula), executive control areas (inferior frontal gyrus and parietal cortex) and movement control regions (precentral sulcus) in these patients.…”
Section: Pseudoseizuresmentioning
confidence: 98%
“…Labate és mtsai a corticalis vastagságot -köztük a szür-keállomány-térfogatot -vizsgálták voxelalapú morfometriával, amely az egészséges kontrollcsoporthoz viszonyítva a PNER-betegek körében szignifikáns corticalis elvékonyodást jelzett a jobb agyfélteke primer motoros és premotoros, valamint a kisagy bilateralis területein [50]. Az eredmények azonban fenntartásokkal kezelen-dők, mivel szinte az összes vizsgálati személyt depresszióval is diagnosztizálták; hasonló strukturális eltéréseket pedig depresszióban is kimutattak [51].…”
Section: Organicitásunclassified